Development of public sector information management systems: challenges and promising practices. Issue 3 (20th August 2018) - Khalid, Hannan; Noor, Asim; Iqbal, Javed; Farid, Shahid; Chang, Victor
Abstract : Purpose: More and more governmental organizations are switching to information systems to enhance their operations and reduce cost but the development of these systems involves a lot of challenges. This paper aims to find out the challenges that project managers have to face during the development of such systems and the practices they can adopt to address these challenges. Design/methodology/approach: To identify the challenges, data have been gathered across six key project management areas. The six targeted key areas are project integration management, project scope management, project time management, project cost management, project human resource management and project communications management. The authors have coordinated with 11 managerial-level IT professionals using semi-structured interviews and have gone through their communication archives. Findings: Findings prove that practices such as focusing on cost reduction, informal congregations, trainings and frequent communication between vendor and client help in addressing the challenges. Furthermore, learning from management experiences of the managers can assist managers in similar role to create a pattern of success while working with governmental projects. Originality/value: The authors peek into the development life cycle of a public sector project named as prison information management system. The project has encountered numerous challenges and has been accomplished in significantly delayed time than designated.